Biomarkers of Inflammation and Lung Recovery in Extracorporeal Membrane Oxygenation Patients With Persistent Pulmonary Hypertension of the Newborn: A Feasibility Study. Issue 4 (April 2020) - Pais, Paolo; Robinson, Simon; Majithia-Beet, Gavin; Lotto, Attilio; Kumar, Tracy; Westrope, Claire; Sullo, Nikol; Eagle Hemming, Bryony; Joel-David, Lathishia; JnTala, Maria; Corazzari, Claudio; Grazioli, Lorenzo; et al.
Abstract : Objectives: Extracorporeal membrane oxygenation is a treatment for Persistent Pulmonary Hypertension of the Newborn with high mortality. Hypothesis: the extracorporeal membrane oxygenation circuit results in inflammatory responses that mitigate against successful weaning. Design: Single-center prospective observational feasibility study. Setting: PICU. Patients: Twenty-four neonates requiring extracorporeal membrane oxygenation support for Persistent Pulmonary Hypertension of the Newborn. Interventions: None. Measurements and Main Results: The reference outcome was death or more than 7 days of extracorporeal membrane oxygenation support. Other outcomes included serial measures of plasma-free hemoglobin and markers of its metabolism, leucocyte, platelet and endothelial activation, and biomarkers of inflammation. Of 24 participants recruited between February 2016 and June 2017, 10 died or required prolonged extracorporeal membrane oxygenation support. These patients were sicker at baseline with higher levels of plasma-free hemoglobin within 12 hours of cannulation (geometric mean ratio, 1.92; 95% CIs, 1.00–3.67; p = 0.050) but not thereafter, versus those requiring less than 7 days extracorporeal membrane oxygenation. Serum haptoglobin concentrations were significantly elevated in both groups. Patients who died or required prolonged extracorporeal membrane oxygenation support demonstrated elevated levels of platelet-leucocyte aggregation, but decreased concentrations of mediators of the inflammatory response: interleukin-8, C-reactive protein, and tumor necrosis factor α. Conclusions: Clinical status at baseline and not levels of plasma-free hemoglobin or the systemic inflammatory response may determine the requirement for prolonged extracorporeal membrane oxygenation support in neonates. Abstract : Supplemental Digital Content is available in the text.